2005
DOI: 10.1002/bit.20631
|View full text |Cite
|
Sign up to set email alerts
|

Compared tolerance to osmotic stress in various microorganisms: Towards a survival prediction test

Abstract: The osmotic tolerance of microbial cells of different microorganisms was investigated as a function of glycerol concentration and temperatures. Cells displayed specific sensitivity to dehydration in glycerol solutions. The viability of Gram-negative strains (Escherichia coli, Bradyrhizobium japonicum), Gram-positive strains (Lactobacillus plantarum, L. bulgaricus), and yeasts (Saccharomyces cerevisiae, Candida utilis) decreased with increasing osmotic pressure. For each strain, a characteristic osmotic pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Similar patterns were observed in cells subject to desiccation, and this suggested that the peptidoglycan layer, thicker in Gram-positive bacteria, was involved in resistance towards osmotic variations (Nocker et al, 2012). Nevertheless, Mille et al (2005) studied the survival rates of 2 yeasts, 2 Grampositive bacteria and 2 Gram-negative bacteria subjected to osmotic variations and demonstrated that cell type alone cannot explain increased tolerance, but that intra-species membrane composition characteristics also have to be considered. The composition in fatty acids notably strongly influences membrane fluidity and its susceptibility to mechanical damages.…”
Section: Osmotic Shocksmentioning
confidence: 68%
“…Similar patterns were observed in cells subject to desiccation, and this suggested that the peptidoglycan layer, thicker in Gram-positive bacteria, was involved in resistance towards osmotic variations (Nocker et al, 2012). Nevertheless, Mille et al (2005) studied the survival rates of 2 yeasts, 2 Grampositive bacteria and 2 Gram-negative bacteria subjected to osmotic variations and demonstrated that cell type alone cannot explain increased tolerance, but that intra-species membrane composition characteristics also have to be considered. The composition in fatty acids notably strongly influences membrane fluidity and its susceptibility to mechanical damages.…”
Section: Osmotic Shocksmentioning
confidence: 68%
“…This competition results in cell growth inhibition and low FOH production. A supply of glycerol can alleviate the shortage of acetyl-CoA, however, extraordinary high glycerol concentrations (e.g., 4% (v/v)), might change the medium properties such as osmosis, which has been reported to affect microorganism viability (Karlgren et al, 2005;Mille et al, 2005). Under such unfavorable condition, the capacity of E. coli to produce FOH might be weakened and led to low FOH production after the addition of 4% (v/v) glycerol.…”
Section: Foh Production From the Entire Synthetic Mva Pathwaymentioning
confidence: 99%
“…The adaptive response of Lb. plantarum WCFS1 to a range of stresses has been investigated, including high temperature (Fiocco et al, 2007), high osmotic pressure (Mille et al, 2005), bile salts (Elkins & Mullis, 2004), low pH (Ingham et al, 2008) and oxidative stress (Serrano et al, 2007). However, the Lb.…”
Section: Introductionmentioning
confidence: 99%